Evaluation of the anti-hyperglycemic and antioxidant activities of a novel phytochemical formulation - Reshma Vijayakumari Raveendran Nair; Karthik Varma; Basil Paul; Augustine Amalraj; Sasikumar Kuttappan (Elsevier, 2021)
Background: One of the major characteristics of Diabetes Mellitus (DM) is high blood glucose levels and impairment of insulin production, which can lead to serious complications, so the main aim of treating patients with diabetes, is to maintain normal levels of glycaemia control. With the adverse effects and limitations of the existing drugs, scientists have been in search for safer and more efficient and affordable alternative treatments. In this backdrop, search for a new generation of antidiabetic drugs is a priority in recent years. Purpose: Natural products base drugs were used in traditional systems of medicine for diabetes. The introduction of drugs based on natural products is usually considered to be safer, cheaper, easily available and sometimes more efficacious than purely synthetic ones. In addition, the synergetic effect of the constituent agents could be better than a single agent acting alone. Accordingly, the aim of the present study was to develop a phytochemical formulation including bioavailable curcuminoids, extracts of Gymnema sylvestre, Emblica officinalis and Salacia reticulata based on traditional knowledge and to evaluate its anti-hyperglycemic and antioxidant activities. Methods: The phytochemical formulation was prepared by using encapsulation technology and the bioactive components were estimated using UPLC. Physical parameters, total phenolic and flavonoid content, antioxidant (DPPH, FRAP, SOD scavenging activity), α-amylase inhibition and blood glucose lowering activity in rats were also evaluated. Results: Oral supplementation at a dosage of 200 mg/kg and 400 mg/kg of phytochemical formulation for a duration of 21 days resulted in a 77.8% and 76.1% reduction in the blood glucose level. The total flavonoid content of 42.92 ± 0.028% QE, DPPH activity showed an IC50 of 93.59 ± 0.88 µg/mL, superoxide radical scavenging activity showed an IC50 of 45.71 ± 0.17 μg/ml, α-amylase inhibitory activity exhibited IC50 value of 1053 ± 1.41 µg/mL all showed promising results for the efficacy of the formulation. Conclusion: Based on the results, the novel phytochemical formulation has potent antidiabetic and antioxidant efficacy, and which can be a promising candidate for the development of new generation antidiabetic drugs.